MODERN ECOLOGICAL INDUSTRY IS A MATTER OF TIME - V. Souponitskiy (Вестник университета)
The alleged transformation in the field of ecology until 2030 are examined in the article. Based on the results achieved in this area in the intervening years since the adoption of the ecological doctrine of the Russian Federation in 2002, the conclusion about the impossibility of achieving the goals necessary to ensure normal conditions for the populations living throughout the country is done. In order to bring about real improvement in the ecological state of the territory the author offers to carry out an environmental megaproject - five-year program of creating a modern environmental industries. Providing the program with human resources can be addressed by environmental program of socialization of the Russian youth through movement «Youth environmental groups».